Inhalation challenge test using pigeon eggs for chronic hypersensitivity pneumonitis. Issue 12 (18th October 2020) - Okuda, Ryo; Takemura, Tamiko; Mikami, Yu; Hagiwara, Eri; Iwasawa, Tae; Baba, Tomohisa; Kitamura, Hideya; Komatsu, Shigeru; Okudela, Koji; Ohashi, Kenichi; Ogura, Takashi
Abstract: Background: Chronic hypersensitivity pneumonitis (CHP) remains a diagnostic challenge. The process of collecting and extracting serum and droppings from causative animals for the inhalation challenge test is complicated and the risk of inducing disease progression exists. Objective: To investigate the utility and safety of an inhalation challenge test using pigeon eggs. Methods: Pigeon eggs were pasteurized and mixed with a saline solution to produce an inhalation fluid. An inhalation challenge test was conducted on 19 patients with bird‐related CHP and 17 patients with interstitial lung disease other than bird‐related CHP. To identify antigens in pigeon eggs, the antigen‐antibody responses of the pigeon eggs and serum from patients were evaluated using Western blotting. Results: The mean changes in C‐reactive protein, alveolar‐arterial oxygen difference, erythrocyte sedimentation rate, and lactate dehydrogenase significantly increased by 0.32 mg/dL ( P = .014), 7.8 Torr ( P = .002), 1.4 mm/h ( P = .012), and 5.4 U/mL ( P = .0019), respectively, in bird‐related CHP group compared to the control 24 hours after the inhalation challenge test. Furthermore, within 24 hours of the inhalation test, the mean forced vital capacity decreased by 2.3% in the bird‐related CHP group compared with a decline of 0.05% in the control group ( P = .035). Serum collected from seven bird‐related CHP patients who underwent the inhalation challenge test and reacted to antigens with molecular weights of 37‐75 KDa, and these molecular weights were consistent with egg albumin and globulin. Conclusion: Since a mild response was observed after the inhalation challenge test using pigeon eggs, this test was an obvious candidate for diagnosing bird‐related CHP.